Razlike v sodelovanju vzgojiteljev in staršev v okoljih z različnim socialno-ekonomskim statusom - Janžekovič Žmauc, Irena (Revija za elementarno izobraževanje, 2014)
Cooperation of Preschool Teachers and Parents – The Differences in Environments with Different Socio-Economics Status. Preschool education is not possible without the cooperation of the parents, because it represents a complement to family education. Socio-economic status of parents is one of the factors that affect the cooperation of preschool teachers and parents. The empirical study checked whether there are differences in the types and frequency of participation of preschool teachers and parents in the areas of two Slovenian statistical regions that differ in the socio-economic status. We found that preschool teachers in the environment with lower socio-economic status more often cooperate with parents in some formal and informal modes of cooperation than they do in the environment with higher socio-economic status.